Sustainable Logistics Management and Operational Efficiency at BIDCO Uganda Limited - Sanyu Bridget Kiwala (Uganda Christian University, 2025)
This study investigated the relationship between sustainable logistics management practices and operational efficiency in manufacturing firms, with a focus on BIDCO Uganda Limited. Specifically, the research sought to: examine the effect of green transportation practices on operational efficiency, assess the influence of eco-friendly warehousing and packaging, and analyze the impact of reverse logistics and waste management on operational efficiency. The study adopted a cross-sectional research design and employed a quantitative research approach. Data was collected through structured questionnaires administered to 59 respondents, selected through simple random sampling from various departments within the firm. The data was coded and analyzed using SPSS, applying both descriptive statistics (frequencies, means, standard deviations) and inferential statistics to draw meaningful conclusions. The standardized coefficient statistics revealed that Reverse logistics and waste management (β= 0.497, t=4.351, p=0.001) was the only significant factor determining operational efficiency at Bidco Uganda limited among the factors considered in the study. green transportation practices (β=0. 175, t=1.637, p=0.107) and Eco-friendly warehousing and packaging (β=0.239, t=1.921, p=0.060) where insignificant because they had the p values greater than 0.01. The study concludes that the adoption of sustainable logistics practices is essential for improving operational efficiency in manufacturing firms. It recommends that manufacturing companies should invest in fuel-efficient and environmentally friendly transport systems, adopt energy-saving and biodegradable warehousing methods, and strengthen reverse logistics frameworks to enhance cost efficiency and promote environmental sustainability
Undergraduate